Seasonal freeze-thaw modulates methane cycling in urban waters revealed by multiple isotopic constraints - Jiaxu Han; Xinchu Wang; Rob M. Ellam; Matthieu Clog; Zhiyong Pang; Heping Lu; Chenyang Shou; Lishan Ran; Si-Liang Li (Water Research, 2026)

The influence of seawater pCO2 and temperature on the amino acid composition and aragonite CO3 disorder of coral skeletons - Nicola Allison; Phoebe Ross; Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Celeste Kellock; Catherine Cole; Matthieu Clog; David Evans; Chris Hintz; Ken Hintz; Adrian A. Finch (Coral Reefs, 2024)
Coral skeletons are composites of aragonite and biomolecules. We report the concentrations of 11 amino acids in massive Porites spp. coral skeletons cultured at two temperatures (25 °C and 28 °C) and 3 seawater pCO 2 (180, 400 and 750 µatm). Coral skeletal aspartic acid/asparagine (Asx), glutamic acid/glutamine (Glx), glycine, serine and total amino acid concentrations are significantly higher at 28 °C than at 25 °C. Skeletal Asx, Glx, Gly, Ser, Ala, L-Thr and total amino acid are significantly lower at 180 µatm seawater pCO 2 compared to 400 µatm, and Ser is reduced at 180 µatm compared to 750 µatm. Concentrations of all skeletal amino acids are significantly inversely related to coral calcification rate but not to calcification media pH. Raman spectroscopy of these and additional specimens indicates that CO 3 disorder in the skeletal aragonite lattice is not affected by seawater pCO 2 but decreases at the higher temperature. This is contrary to observations in synthetic aragonite where disorder is positively related to the aragonite precipitation rate mediated by either increasing temperature (this study) or increasing Ω (this study and a previous report) and to the concentration of amino acid in the precipitation media (a previous report). We observe no significant relationship between structural disorder and coral calcification rate or skeletal [amino acid]. Both temperature and seawater pCO 2 can significantly affect skeletal amino acid composition, and further work is required to clarify how environmental change mediates disorder.

B(OH)4− and CO32− do not compete for incorporation into aragonite in synthetic precipitations at pHtotal 8.20 and 8.41 but do compete at pHtotal 8.59 - Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Adrian A. Finch; Matthieu Clog; Ed Hathorne; Nicola Allison (Geochimica et Cosmochimica Acta, 2024)

Clumped isotope and Δ17O measurements of carbonates in CM carbonaceous chondrites: New insights into parent body thermal and fluid evolution - Matthieu Clog; Paula Lindgren; Sevasti Modestou; Alex McDonald; Andrew Tait; Terry Donnelly; Darren Mark; Martin Lee (Geochimica et Cosmochimica Acta, 2024)

Insights into the response of coral biomineralisation to environmental change from aragonite precipitations in vitro - Cristina Castillo Alvarez; Kirsty Penkman; Roland Kröger; Adrian A. Finch; Matthieu Clog; Alex Brasier; John Still; Nicola Allison (Geochimica et Cosmochimica Acta, 2024)